2018
DOI: 10.1371/journal.pone.0192982
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk during pregnancy and postpartum periods among HIV-infected and –uninfected South African women: Implications for primary and secondary HIV prevention interventions

Abstract: BackgroundHIV acquisition in pregnancy and breastfeeding contributes significantly toward pediatric HIV infection. However, little is known about how sexual behavior changes during pregnancy and postpartum periods which will help develop targeted HIV prevention and transmission interventions, including pre-exposure prophylaxis (PrEP).MethodsCross-sectional study in HIV-infected and uninfected pregnant and postpartum women in Cape Town, South Africa. Interviewers collected survey data on demographic, sexual beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Seven studies did not indicate the study population age [35, 81, 100102]. Overall, 46 studies included both male and females [35, 3748, 5156, 59, 64–66, 68, 70, 73, 78, 80, 84, 87, 92, 94, 101, 102, 111, 114, 120, 126–129, 134, 136], 51 studies included women/girls only [36, 49, 50, 57, 58, 6063, 67, 69, 71, 72, 74, 76, 77, 79, 8183, 8591, 9699, 105, 106, 109, 110, 112, 113, 115119, 121, 132, 133, 135], and eight studies included men/boys only [75, 93, 95, 107, 108, 130, 131, 137].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies did not indicate the study population age [35, 81, 100102]. Overall, 46 studies included both male and females [35, 3748, 5156, 59, 64–66, 68, 70, 73, 78, 80, 84, 87, 92, 94, 101, 102, 111, 114, 120, 126–129, 134, 136], 51 studies included women/girls only [36, 49, 50, 57, 58, 6063, 67, 69, 71, 72, 74, 76, 77, 79, 8183, 8591, 9699, 105, 106, 109, 110, 112, 113, 115119, 121, 132, 133, 135], and eight studies included men/boys only [75, 93, 95, 107, 108, 130, 131, 137].…”
Section: Resultsmentioning
confidence: 99%
“…Only six (two from South Africa and one each from Nigeria, Rwanda, Zambia and Zimbabwe) out of the 51 oral sex studies described the prevalence of reported oral sex as either giving or receiving oral sex [36, 37, 39, 69, 71, 72]. Most studies that reported on prevalence of oral sex were from South African region, among adolescents and young adults, and key affected populations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraception has been one of the reasons described in the literature for practicing anal sex but there is no reason described for a higher prevalence of oral sex. A recent study carried out in South Africa among pregnant and postpartum women showed that during pregnancy 44% reported oral sex and 8% anal sex; and 49% and 11%, respectively at postpartum [9]. Teasdale et al found in a study carried out with pregnant women from Zimbabwe and South Africa, that pregnancy decreased sexual activity and high-risk sex, including anal sex [49].…”
Section: Discussionmentioning
confidence: 99%
“…For females of reproductive potential, sex that could lead to HIV infection may also result in pregnancy. Conversely, the perinatal period is a time of heightened risk for new HIV infection [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%